Permanent Residency and Refugee Immigrants' Skill Investment - Jacob Nielson Arendt; Christian Dustmann; Hyejin Ku (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze an immigration reform in Denmark that tightened refugee immigrants' eligibility criteria for permanent residency to incentivize their labor market attachment and acquisition of local language skills. Contrary to what the reform intended, the overall employment of those affected decreased while their average language proficiency remained largely unchanged. This was caused by a disincentive effect, where individuals with low pre-reform labor market performance reduced their labor supply. Our findings suggest that stricter permanent residency rules, rather than incentivizing refugees' skill investment, may decrease the efforts of those who believe they cannot meet the new requirements.
Keywords: J22; J24; J61; 330; immigrant assimilation; refugee integration; labor supply; language proficiency; human capital